Formation à la conduite routière: approche socio-langagière des leçons de conduite - Carcassonne, Marie; Servel, Laurence (My University, 2009)
We analyze different forms of scaffolding in a quite specific training situation: driving lessons in a driving school which plays a mediating role towards social insertion. We first develop an interactional and developmental approach to driving lessons and propose to see these practices as tutoring interactions. Then, we elaborate a typology of forms of scaffolding based on the analysis of our data, that seem to help the learning and driving process at different levels. An analysis of two excerpts serves to illustrate how monitors combine these various forms of scaffolding in the situated dynamic of their practice. We conclude by arguing that the concept of scaffolding can be profitably mobilised in the context of adult education.
Keywords: Scaffolding; adult education; driving lessons; linguistic interaction; sociolinguistic approach